2015
DOI: 10.17096/jiufd.24298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Sealing on Stain Resistance of a Nano-Hybrid Resin Composite

Abstract: Purpose:This study investigated the influence of sealant application on stain resistance of a nanohybrid resin composite compared to the efficacy of a bonding agent used as a surface sealant on prolonging color stability of the resin composite.Materials and Methods:28 disc-shaped materials were prepared from a nano-hybrid resin composite Filtek Z550 and assigned to four groups: G1K: nonsealed; G2:Adper Single Bond; G3: Fortify ; G4: Biscover LV. After 24 h storage in distilled water at 37˚C, all specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
6
0
11
Order By: Relevance
“…The staining ability of coffee has been explained by authors in terms of the polar colorants of coffee having both an absorption and an adsorption effect on the surface of resin-based materials, as well as the organic phase of resin composites. 36,37 The level of absorption and penetration of yellow colorants existing in coffee were due to the compatibility of the materials' polymer matrix. 38 Another possible color change mechanism of resin composites could be the pH of the solutions in which they were immersed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The staining ability of coffee has been explained by authors in terms of the polar colorants of coffee having both an absorption and an adsorption effect on the surface of resin-based materials, as well as the organic phase of resin composites. 36,37 The level of absorption and penetration of yellow colorants existing in coffee were due to the compatibility of the materials' polymer matrix. 38 Another possible color change mechanism of resin composites could be the pH of the solutions in which they were immersed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Filtek Bulk Fill had significantly higher color resistance than Solitaire 2, Tetric N‐Ceram, and SonicFill when immersed in coffee and those specimens demonstrated greater discoloration than clinically acceptable threshold at 1‐month period. The staining ability of coffee has been explained by authors in terms of the polar colorants of coffee having both an absorption and an adsorption effect on the surface of resin‐based materials, as well as the organic phase of resin composites . The level of absorption and penetration of yellow colorants existing in coffee were due to the compatibility of the materials' polymer matrix…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Optidiscs were used for polishing, and a surface sealant, BisCover LV, was used to glaze the specimens after the polishing system. One of the main reasons of manufacturing these low-viscosity surface sealants is that they have the ability to cover up micro porosities and to complete surface integrity (10). Based on the results at every time period, the glazed groups of all composites had lower roughness values than the polished groups.…”
Section: Resultsmentioning
confidence: 99%
“…Although all of these polishing instruments produce a glossy surface on resin composite restorations, it has been reported that the polishing instruments can also leave irregularities on the surface in different degrees (7,9). To eliminate these irregularities, filling the microporosities and microgaps, surface sealing could be used (10,11). These materials can easily penetrate through the microcracks and irregularities formed during the finishing and polishing procedures because of low viscosity and wettability characteristics (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Es por este motivo que a la comparación con el Camu Camu y Aguaje, los cuales también presentan betacaroteno en su composición, atribuimos el cambio de coloración de las resinas. (4,35,37) En el Perú, las bebidas con frutos de la Amazonía son parte del consumo diario en la población, por ser considerados saludables y naturales. (40) Sin embargo, no existe evidencia científica sobre la estabilidad cromática en resinas compuestas inmersas a las sustancias amazónicas pese a la utilización de estas en el país.…”
Section: Dedicatoriaunclassified